Cyclodextrins and Amino Acids Enhance Solubility and Tolerability of Retinoic Acid/Tretinoin: Molecular Docking, Physicochemical, Cytotoxicity, Scratch Assay, and Topical Gel Formulations Investigation - Zeinab Fathalla; Mai E. Shoman; Hebatallah S. Barakat; Adel Al Fatease; Ali H. Alamri; Hamdy Abdelkader (MDPI AG, 2024)
With increasing longevity globally, the search for effective and patient-friendly anti-aging solutions has been growing. Retinoic acid (Ret) is an FDA-approved anti-aging and anti-wrinkling formula, however, its poor solubility and poor tolerability hamper its use in cosmetically accepted formulations. In this study, cyclodextrins and arginine were investigated for improving the solubility and tolerability of retinoic acid through the formation of inclusion complexes and salt formation, respectively. Two different methods were employed: physical mixing and kneading. The prepared dispersions were investigated for molecular docking (MD), solubility, thermal and spectral analyses, cytotoxicity, and scratch assays. The optimized disperse systems were formulated in a gel formulation and characterized for rheological, in vitro release, and kinetics. The MD, DSC, and FTIR results indicated that both β- and hydroxy propyl (HP) β-cyclodextrins could host RA in their cavities and form inclusion complexes. Ret can form a salt with the basic amino acid arginine. Solubility studies of RA significantly (p < 0.01) enhanced by 14- to 81-fold increases with the investigated cyclodextrins and arginine. The cell viability recorded for Ret:HP β-CD K and Ret:arginine K was significantly increased compared to that for Ret alone. The IC50% recorded for azelaic acid (mild to non-irritant control), Ret, Ret:HP β-CD K, and Ret:arginine K were 1000, 485, 1100, and 895 µg/mL, respectively. The two carriers (HP β-CD and the amino acid arginine) were able to significantly (p < 0.05) reduce the irritation potential of Ret. Furthermore, comparable gap closure rates were recorded for Ret alone, Ret:HP β-CD K, and Ret:arginine K, indicating that inclusion complexation and ion pair formation reduced the irritation potentials without undermining the efficacy.